Desenvolvimento e categorização do pensamento computacional docente com o uso da cultura maker em ambientes computacionais construcionistas - Caratti, Ricardo Lima (2023)
Computational Thinking, in the context of education, has been considered as a teaching approach that contributes to the development of fundamental skills, such as understanding, analyzing, defining, modelling, comparing, and solving problems. However, according to several recent studies, the implementation of this teaching approach in basic education is still a challenge, especially in teacher training. Thus, the purpose of this study is to analyze how the process of appropriation of Computational Thinking concepts by basic education teachers occurs, through the application of a training course. To support the training process, principles and ideas of the maker culture and resources such as Arduino and the Scratch language will be used. Therefore, to get the objectives of this study, it will be necessary to assess how elementary school teachers understand Computational Thinking, their abilities, and difficulties, and describe their practices before and after their participation in the formative stage. The study conducted was predominantly of a qualitative nature and was divided into the following stages: 1) an exploratory bibliographic study; 2) a pre-test applied to a group of selected teachers; 3) a training course for the selected teachers; and 4) a post-test applied to the teachers. The method used for inferences will be Content Analysis. As a contribution to the teaching and approach of Computational Thinking and Maker Culture in the school environment, it is intended to develop a software product that will be able to guide teachers in their classroom practices. Finally, this study aims to make teachers feel more confident using Computational Thinking in their teaching practices.